2006
DOI: 10.1021/bi0610552
|View full text |Cite
|
Sign up to set email alerts
|

The Vault Exterior Shell Is a Dynamic Structure that Allows Incorporation of Vault-Associated Proteins into Its Interior

Abstract: Vaults are 13 million Dalton ribonucleoprotein particles with a highly conserved structure. Expression and assembly by multimerization of an estimated 96 copies of a single protein, termed the major vault protein (MVP), is sufficient to form the minimal structure and entire exterior shell of the barrel-shaped vault particle. Multiple copies of two additional proteins, VPARP and TEP1, and a small untranslated vault RNA are also associated with vaults. We used the Sf9 insect cell expression system to form MVP-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
114
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(125 citation statements)
references
References 42 publications
(105 reference statements)
4
114
0
Order By: Relevance
“…It was demonstrated that the monomers of different proteins can be differentiated from their respective oligomers (dimers, trimers) and that there was a strong correlation between the molecular weight and the mobility diameter determined using ES-DMA. Since then, the molecular weightmobility diameter empirical correlation plotted in Figure 3.1 has been confirmed by several groups of researchers for both globular, as well as non-globular proteins ranging from a few kDa [11,19,56,57] to several MDa [56]. The actual expression is later going to be used in Chapter 8.…”
Section: 2polymers and Proteinsmentioning
confidence: 64%
See 1 more Smart Citation
“…It was demonstrated that the monomers of different proteins can be differentiated from their respective oligomers (dimers, trimers) and that there was a strong correlation between the molecular weight and the mobility diameter determined using ES-DMA. Since then, the molecular weightmobility diameter empirical correlation plotted in Figure 3.1 has been confirmed by several groups of researchers for both globular, as well as non-globular proteins ranging from a few kDa [11,19,56,57] to several MDa [56]. The actual expression is later going to be used in Chapter 8.…”
Section: 2polymers and Proteinsmentioning
confidence: 64%
“…It has also been used to gain insight into the function of a number of protein complexes such as vault proteins [56], 20S…”
Section: 2polymers and Proteinsmentioning
confidence: 99%
“…In particular, peptide and protein folding (2,4,(9)(10)(11)(12)(13)(14) and amyloidogenic misfolding (15) were explored. Application of IMS and IMS/MS is expanding to ever-larger macromolecules, including noncovalent assemblies with mass (m) Ͼ 1 MDa (16)(17)(18). Such studies have used both drift tube (DT) IMS (1)(2)(3)(4)(5)(7)(8)(9)(10)(11)(12)(13)(14)(15) and differential mobility analyzers (DMA) (17,18) to separate ions by absolute mobility (K).…”
mentioning
confidence: 99%
“…Application of IMS and IMS/MS is expanding to ever-larger macromolecules, including noncovalent assemblies with mass (m) Ͼ 1 MDa (16)(17)(18). Such studies have used both drift tube (DT) IMS (1)(2)(3)(4)(5)(7)(8)(9)(10)(11)(12)(13)(14)(15) and differential mobility analyzers (DMA) (17,18) to separate ions by absolute mobility (K). In DT IMS, ions are separated while being pulled through still gas by an electric field.…”
mentioning
confidence: 99%
See 1 more Smart Citation